Interpretasi Data Log Sumur X-15 Lapangan Y Untuk Penentuan Awal Isi Hidrokarbon Di Tempat - hendra budiman; Dian Pratiwi Harisun (Politeknik Akamigas Palembang, 2016)
The estimation of hydrocarbon reserves the most fundamental thing prior to plan of field development to determine the economics of an oil or gas field. Well logging is a tool that is run into teh well to measure the density, resistivity and conductivity of the formations at the time of the drilling of the well. From the data interpretation WLX-15 well resulted an average porosity of 14% and average water saturation of 0.4. Initial oil in place (in STB) per acre of zone – 4 are 236 536 devided by oil formation volume factor, while from the smallest zone-9 the initial oil in place (in STB) by area are 9727,7 devided by the oil formation volume factor.